Development of the scale of psychosocial factors in food allergy (SPS‐FA). Issue 7 (12th September 2013) - Cortes, Aaron; Castillo, Angela; Sciaraffia, Alicia
Abstract Background Food allergy (FA) is a growing condition among children and it's psychological impact over the patients and their caregivers is well known, establishing a vicious circle that perpetuates stress levels. However, psychosocial factors are not commonly included in allergy treatments. Based on the lack of evidence of records about a scale that indicates the level of interaction between biopsychosocial factors in the patient–caregivers dyad for FA, the present research aims to develop a scale with these characteristics as a helpful tool to achieve a more comprehensive system of health care. Methods A preliminary 28‐item scale was generated (sample N = 99). The scale was adjusted in contents and language after expert opinion and application on patients. A factor analysis was carried out selecting the items from the final scale. Results The final 9‐item scale included three areas: impact on quality of life, social impact and conflicts. The scale had a good internal consistency (Cronbach's α = 0.870) and correlated significantly with anxiety and depression measurements. Moreover, it was able to discriminate between study groups (members and non‐members of peer support groups) and proved construct validity. Conclusions The SPS‐FA is the first scale for the assessment of the interaction of biopsychosocial factors on FA that includes the patient–caregiver dyad. Its application might be relevant for future research, and it can provide the clinician and the researcher with a solid tool to define which type of psychosocial support is required to provide a more comprehensive care in FA.